Palladium-Catalyzed Asymmetric Decarboxylative Cycloaddition of Vinylethylene Carbonates with Electrophiles: Construction of Quaternary Stereocenters - Khan, Ajmal; Zhang, Yong Jian (Synlett, 2015)
The enantioselective construction of quaternary stereocenters still remains significant challenge in organic synthesis. Herein, an efficient synthetic strategy for the construction of quaternary stereocenters via palladium-catalyzed asymmetric decarboxylative cycloaddition of vinylethylene carbonates (VEC) with unsaturated electrophiles is highlighted. The processes that enable rapid access to methylene acetal protected tertiary vinylglycols, carbonyl-protected β-substituted β-vinylglycinols, and multifunctionalized tetrahydrofurans bearing continuous tertiary and vicinal all-carbon quaternary stereocenters in high yields with high levels of stereoselectivities.
Keywords: asymmetric catalysis; quaternary stereocenters; palladium; decarboxylative cycloaddition; vinylethylene carbonates